2006
DOI: 10.1093/carcin/bgl221
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin suppresses human osteosarcoma MG-63 cell invasion by inhibiting the ERK-dependent c-Jun/AP-1 induction of MMP-2

Abstract: Silibinin is a natural flavonoid antioxidant with anti-hepatotoxic properties and pleiotropic anticancer capabilities. We tested the hypothesis that silibinin inhibits cellular invasiveness by down-regulating the focal adhesion kinase (FAK) and extracellular signal-regulated protein kinase (ERK)-dependent c-Jun/activator protein-1 (AP-1) induction, which leads to inhibition of urokinase-type plasminogen activator (u-PA) and matrix metalloproteinase-2 (MMP-2) expressions in human osteosarcoma MG-63 cells. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
117
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 43 publications
7
117
0
Order By: Relevance
“…We demonstrated that, silibinin could inhibit the migration and invasion of RCC cells induced by EGFR signaling via blocking of EGFR/MMP-9 signaling. However, two other EGFR signaling downstream proteins, STAT3 and AKT, were not affected by silibinin, which is in agreement with previous results that silibinin inhibited cell migration and invasion through ERK1/2 signal, not AKT and STAT3 phosphorylation (12,22,23).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We demonstrated that, silibinin could inhibit the migration and invasion of RCC cells induced by EGFR signaling via blocking of EGFR/MMP-9 signaling. However, two other EGFR signaling downstream proteins, STAT3 and AKT, were not affected by silibinin, which is in agreement with previous results that silibinin inhibited cell migration and invasion through ERK1/2 signal, not AKT and STAT3 phosphorylation (12,22,23).…”
Section: Discussionsupporting
confidence: 92%
“…Besides its antiproliferative effect, silibinin also show antimetastatic effects on a variety of malignant tumors including prostate cancer, lung cancer, breast cancer, osteosarcoma and oral cancer (11)(12)(13)21,22). Still little is known about suppression effect of silibinin on EGFR signal-induced RCC migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…48 It is of fundamental importance that, to be clinically useful, the antineuropathic agents must reduce the neurotoxic effect of the chemotherapeutic agent maintaining its full anti-tumor efficacy. In this light, silibinin shows a cancer chemopreventive role in both in vitro 10,21 and in vivo 40,46 models. It modulates the imbalance between cell survival and apoptosis through interference with the expressions of cell cycle regulators and proteins involved in apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…26 In addition, an anti-metastatic activity for silibinin has been also described. 11,21 A recent report of the USA National Toxicology Program 33 describes the results of repeated treatments of rats with sylibum marianum extract (containing 65% sylimarin, therefore 30-40% silibinin). 1 No toxic effects have been shown after daily per os administration of 2,500 mgkg À1 extract for 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore examined the role of AP-1 in CAGE-promoted cellular invasion. AP-1 plays many roles during cellular invasion, including as a down-http://bmbreports.org stream target of ERK (9) and as an inducer of MMP-2 in osteocarcinomas (10). AP-1 is further necessary for angiopoietinpromoted endothelial migration (11).…”
Section: Cage Induces Fra-1 By Activating Erk and Mmp-2 Through The Amentioning
confidence: 99%